Tight junction between endothelial cells: the interaction between nanoparticles and blood vessels - Zhang, Yue; Yang, Wan-Xi (Beilstein Journal of Nanotechnology, 2016)
Since nanoparticles are now widely applied as food additives, in cosmetics and other industries, especially in medical therapy and diagnosis, we ask here whether nanoparticles can cause several adverse effects to human health. In this review, based on research on nanotoxicity, we mainly discuss the negative influence of nanoparticles on blood vessels in several aspects and the potential mechanism for nanoparticles to penetrate endothelial layers of blood vessels, which are the sites of phosphorylation of tight junction proteins (claudins, occludins, and ZO (Zonula occludens)) proteins, oxidative stress and shear stress. We propose a connection between the presence of nanoparticles and the regulation of the tight junction, which might be the key approach for nanoparticles to penetrate endothelial layers and then have an impact on other tissues and organs.
Keywords: blood vessels; endothelial cells; nanoparticles; oxidative stress; tight junction